A preliminary study: matrix metalloproteinase expression as an indicator of the hazards of shisha (nargila) smoking - Kaddah, Safy; Rashed, Lila; Obaia, Eman; Sabry, Dina (Archives of Medical Science, 2009)
Introduction: There is a shift in the behaviour of many cigarette smokers to smoke tobacco by shisha because of a false belief that it is a safe way to smoke tobacco. Material and methods: In this work we aimed to study the effect of smoking tobacco by shisha compared to cigarette smoking and to verify the hazardous effects of smoking shisha, by estimation of matrix metalloproteinase (MMP-2 and MMP-9) gene expression in BAL of COPD patients. From 32 COPD patients smoking cigarettes, shisha and combined cigarettes and shisha BAL fluid was obtained, and MMP-2 and MMP-9 were analyzed by reverse transcription polymerase chain reaction. Results: Expression of MMP-2 and MMP-9 was as high in the shisha and combined cigarette and shisha smokers as the cigarette smokers, with a sig-nificant positive correlation between MMP-2 and MMP-9 only in the shisha smoker group. The mean FEV1 (% predicted) of the shisha smoker group was significantly lower compared to the cigarette smoker group. In the shisha smoker group there was a significant statistical difference between severe cases and mild/moderate cases in both MMP-2 and MMP-9 expression. Also, MMP-2 and MMP-9 expression were lower in ex-smokers compared to those with an active smoking habit. Conclusions: Smoking shisha induces expression of metalloproteinases in BAL as much as in smoking cigarettes; moreover, it has a highly deleterious effect on pulmonary function.